An Amudian Oddity: A Giant Biface from Late Lower Palaeolithic Qesem Cave. (20th October 2013) - Barkai, Ran; Gopher, Avi; Solodenko, Natalya; Lemorini, Cristina
Abstract : The paper reports the discovery of an extraordinary flint implement—a large biface—and discusses its significance in the context of Qesem Cave in particular and the late Lower Palaeolithic Acheulo-Yabrudian Cultural Complex of the Levant in general. We contend that this unusually large biface was discarded in an unfinished and unused state, most probably due to a collapse event that took place at the cave some 280, 000 years ago.